1997
DOI: 10.1002/hep.510260725
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of hepatitis C: Other options

Abstract: Because current standard therapy of chronic hepatitis C ultimate therapeutic goal continues to be eradication of all detectable virus in the blood, liver, or other organs. However, with alpha interferon is less than ideal, numerous other approaches have been studied. Iron in the liver, particularly that because of the ability of hepatitis C virus (HCV) to mutate rapidly and become resistant to antiviral agents and immune found in vascular endothelial cells of portal tracts, has been associated with decreased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 4 publications
2
28
2
Order By: Relevance
“…Therefore, when a patient is found to have an active form of CHC, iron reduction therapy should be recommended as an alternative to antiviral agents. 33 Once iron reduction therapy for CHC is authorized in Japan, great benefit might be provided for patients who need adjuvant therapy other than IFN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when a patient is found to have an active form of CHC, iron reduction therapy should be recommended as an alternative to antiviral agents. 33 Once iron reduction therapy for CHC is authorized in Japan, great benefit might be provided for patients who need adjuvant therapy other than IFN.…”
Section: Discussionmentioning
confidence: 99%
“…26,27) In Europe and the United States, individuals with C282Y mutation are so common that ironinduced oxidative stress and its prophylaxis are major issues even in patients with CHC. Bonkovsky, in a review of other options to IFN in CHC, 5) recommended iron reduction therapy as the first line among various regimens including ursodeoxhycholic acid and herbal medicines.…”
Section: Discussionmentioning
confidence: 99%
“…tients fail to respond to these treatments and require additional treatment. 5) The therapeutic effects of iron reduction therapy on CHC, 6,7) which we first empirically introduced based on lysosomal iron stores detected under an Xray microanalyzer, 8) suggested that most patients are exposed to iron-induced oxidative stress. This is particularly important for male patients with a positive balance of iron.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to high levels of Cu results in various changes in the liver tissues that are consistent with oxidative damage to membranes and molecules. Lipid peroxidation causes dysfunction in the cell membrane, decreased fluidity, inactivation of enzymes and changes ion permeability [10,11]. Hatano studied that Cu accumulation in fibrotic livers caused by chronic hepatitis C may contribute to hepatic injury [12].…”
Section: Introductionmentioning
confidence: 99%